Getting at the core of the common core with social studies - Turner, Thomas N.; Clabough, Jeremiah; Cole, William (Teaching and learning social studies., 2015)
For social studies teachers reeling from the buffeting of top-down educational reforms, this volume offers answers to questions about dealing with the Common Core State Standards (CCSS). Each chapter presents and reviews pertinent standards that relate to the social studies. Each chapter also deals with significant topics in the social studies from various social sciences to processes such as inquiry to key skills needed for success in social studies such as analysis and literacy.The most important aspect of these chapters though is the array of adaptable activities that is included in each chapter. Teachers can find practical approaches to dealing with CCSS across the social studies panorama. The multiple authorships of the various chapters mean a variety of perspectives and viewpoints are presented. All of the authors have fought in the trenches of K-12 public education. Their activities reflect this in a way that will be useful to novice or veteran teachers.